Penerapan Metode Audiolingual dalam Pembelajaran Keterampilan Menyimak Bahasa Arab secara Daring: Studi Kasus di SMPIT Adzkia Padang - Sri Indah Lestari; Yasmadi Yasmadi; M. Taufiqurrahman (Alsina : Journal of Arabic Studies, 2024)
This study aims to investigate the implementation of the audiolingual method in teaching Arabic listening skills at SMPIT Adzkia Padang during the COVID-19 pandemic. The research employs a qualitative descriptive approach, with data collected through structured observations and in-depth interviews with eighth-grade students and Arabic language teachers. The findings reveal that the audiolingual method positively impacts students' listening skills, with nearly 90% of students being able to memorize, recall, and use the sentences or texts taught. However, online learning and time constraints posed challenges to the optimal application of this method. Teacher perceived the audiolingual method as less effective for online learning and suggested that lecture-based methods were more suitable for explaining theoretical concepts. The study also found that the Arabic learning guidebook needed to be aligned with the students' proficiency levels, which hindered the learning process. These findings provide educators with insights regarding the audiolingual method's strengths and limitations, emphasizing the importance of adapting teaching methods to the context and students' needs.